Beyond WTO: Meeting the Challenges of the New Trade and Environment Regime, Perspectives from the Philippines and the ASEAN - Ponciano Jr. S. Intal; Edwin del Valle; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 1996)
Using the principle of subsidiary and the general rule of optimal intervention, this paper reviews the current discussion in the WTO on resolving the issues of environment-related trade and trade-related environmental measures with the rules of the multilateral trading system. Economic growth, environmental protection and international competitiveness in the context of the Philippines and other ASEAN countries are also discussed.
Keywords: 330; trade sector; ASEAN; ASEAN tariffs